ANALISIS KINERJA PEMUNGUTAN PAJAK DAN RETRIBUSI DAERAH DALAM RANGKA MENINGKATKAN PENERIMAAN PAJAK DAERAH : Studi Kasus Pada Unit Pelayanan Pajak dan Retribusi Daerah Kelapa Gading - Eveline Meylani (2020)
This research was conducted to determine the Performance of Tax Collection and Regional Retribution. This research was conducted at the Kelapa Gading Regional Tax and Retribution Service Unit (UPPRD). The method used is descriptive qualitative method, interpretive paradigm. Data collection techniques used were observation, interviews and documentation. The research result is known that there are two criteria in the assessment of Tax Collection Performance. The two criteria are the Effectiveness Criteria and the Criteria for Contribution to PAD DKI Jakarta. Research Results Prove that in the last three years 2017, 2018, and 2019 the performance of UPPRD Kelapa Gading was classified as Not Effective because it did not reach the target. The results of the study also prove that the Regional Tax and Retribution Revenues have an Enough Contribution to the Original Revenue of DKI Jakarta. Research results prove that the lack of public awareness in complying with tax regulations is a major factor in not achieving the target of realization of revenue from Regional Taxes and Retribution. UPPRD Kelapa Gading needs to do more intense socialization so that people are aware of their obligations to pay taxes, because in the socialization of tax officials can find out the obstacles - taxpayers in paying taxes